Integridade biótica de fragmentos florestais em matriz urbana - Galvani, Fabricio (2018)
In Brazil, semi-deciduous seasonal forest (SSF) is one of the physiognomies of Atlantic Forests, and sited between the Atlantic Forest and Savanna Biomes. Over the last decades, SSF has been fragmented by use of the soil for agricultural or urban areas. The urban and industrial growth promote a strong impact in forest fragments due to the edge effects, isolation, and habitat degradation. Hence, the knowledge about ecologic dynamics and biotic integrity inside this fragment is essential to guide public policy and to support decision makers, in the planning and management of territories. The goal of this study was to analyze the Biotic Integrity in fragments of SSF inside Ribeirão Preto (SP), a medium-sized city in the southeast of Brazil, and to analyse the relationship between BII and landscape metrics (size, shape and connectivity). The method (BII) has nine indicators (littler and grass cover, stand of dead trees, exotic wood species, vines, gaps in the canopy, vascular epiphytes, later species in canopy and in understory). The results can vary from 9 to 45. The survey was carried out in 9 forest fragments, the sizes of which are from 1,3 to 185,0 ha, all with urban influence. The relation between IBI and landscape metrics (size, shape) were analyzed by the Pearson correlation. BII value were registered from 26,0 to 38,0 or as low, medium or high integrity. The results showed strong correlation between IBB and size (p= 0, 7944), and weakness with shape (p= 0, 47). Therefore, the results show a vast area (77 ha) with low Integrity and another small area (22 ha) with high integrity. It was registered a medium-sized area, with high integrity located urban area in expansion, for which it was recommended the creation of one Protected Area.